PELAKSANAAN PROSES LEGALISASI TANAH MELALUI PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DAN PERAN KEPALA DESA DI DESA BAJANG, KECAMATAN MLARAK, KABUPATEN PONOROGO - Putra Anugerah Wibowo; Aditia Wahyu Kurniawan; Khoirurrosyidin; Ekapti Wahjuni Djuwitaningsih (UIR PRESS, 2023)
This study aims to determine the role of the village head in land legalization through the PTSL program in Bajang Village, Mlarak Ponorogo District and to find out the obstacles in the implementation of land legalization through Complete Systematic Land Registration (PTSL) in Bajang Village, Mlarak Ponorogo District. This type of research uses qualitative research methods. The essence of qualitative research is that this research procedure produces descriptive data in the form of written or spoken words from people and observed behavior as well as efforts to find solutions to problems by describing events based on existing facts or evidence. The result of this research is that the role of the Village Head in carrying out Complete Systematic Land Registration or PTSL activities in Bajang Village, Mlarak District, Ponorogo Regency is quite good, as can be seen from the success of the Inventory of Ownership of Ownership of Land Use and Utilization, as well as from the data obtained. The community as applicants and recipients of certificates is very proactive in every activity carried out by the village head and is greatly helped by the implementation of PTSL. In the implementation of the Complete Sitematic Registration or PTSL activity in Bajang Village, no significant obstacles were found. This is based on the opinion of the Bajang Village community itself that the Village Head carries out several activities such as socializing this PTSL activity to the community so that the community understands. Seeing the Bajang Village Head who is so diligent in providing socialization about PTSL activities, inviting the community to contact via telephone or whatsaap at any time, and providing solutions when there is a problem, would it be an example for other Village Heads.